2008
DOI: 10.1524/zkri.2008.0034
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of metastable linkage isomers of six-coordinate ruthenium nitrosyl complexes

Abstract: The linkage isomers of the [M(NO)(CN) 5 ] 2-(M ¼ Fe, Ru, Os), [Ru(NO)Cl 5 ] 2-, trans-[Ru(NO)(NH 3 ) 4 (L)] qþ (L ¼ NH 3 , H 2 O, nicotinamide, imidazole, pyridine, pyrazine, NO 2 -, OH -, Cl -), and trans-[Ru(NO)L 4 (OH)] q (L ¼ pyridine, NO 2 -) ions are studied by density functional theory. DFT calculations show that the electronic ground-state potential surface of these nitrosyl complexes has the local minima corresponding to h 2 -NO and h 1 -O linkage isomers, of which the former is characterized by lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…But for MS1 this argument no longer holds, since the charge on the NO ligand is reduced by 0.07e with respect to GS and the change in bond length amounts to only 0.002 Å. Already Sizova and coworkers 30 discussed this discrepancy between the calculated and experimental results for the vibrational frequencies, which occur especially for MS1. They investigated the influence of the environment by applying a polarizable continuum model Table 7 Experimental (T = 10 K) and DFT calculated vibrations in MS1, differences D(Iso) between isotopes and D( 14 N) between measured/calculated 14 (PCM), which nevertheless did not resolve the issue for MS1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But for MS1 this argument no longer holds, since the charge on the NO ligand is reduced by 0.07e with respect to GS and the change in bond length amounts to only 0.002 Å. Already Sizova and coworkers 30 discussed this discrepancy between the calculated and experimental results for the vibrational frequencies, which occur especially for MS1. They investigated the influence of the environment by applying a polarizable continuum model Table 7 Experimental (T = 10 K) and DFT calculated vibrations in MS1, differences D(Iso) between isotopes and D( 14 N) between measured/calculated 14 (PCM), which nevertheless did not resolve the issue for MS1.…”
Section: Discussionmentioning
confidence: 99%
“…In such a simple picture, the contribution of the coupling between ñ(RuN) and ñ(NO) to the experimentally observed values is neglected. As a matter of fact, Sizova et al 30 indicated the contributions of the internal coordinates to the NO and RuNO vibrations for the [RuCl 5 NO] 2À complex, which amounts up to 11% of ñ(RuN) to 89% ñ(NO) in GS using a valence force model, but without proceeding to a detailed analysis including further calculations of local force constants. Such a complete decoupling for the solid state by the transformation of all vibrations into a pure two-atomic behavior can be obtained by using the local vibrational mode theory formalism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation